Enhancing Learner Autonomy in Extensive Listening Class through the Listening Logs - Faizatul Istiqomah (Jurnal Bahasa Lingua Scientia, 2020)
Abstract: Mastering listening skill has been a great burden for intermediate to upper-intermediate students in Indonesian EFL context. The absence of real life exposures to native speakers of English strengthens student’s reluctance to frequently practice listening to English. Therefore, this paper will propose the listening logs applied in an extensive listening class to enhance student’s autonomy in improving their listening skill. The article will begin by highlighting some challenges faced by students in Listening class and some possible strategies to deal with them will be presented further. Later, relevant theories on extensive listening and learner autonomy will be discussed. Next, the author will introduce the listening logs followed by the procedures on how this is planned, implemented and evaluated. This paper offers an alternative for teachers to promote students’ in and out of class learning regarding their own pace and interest in extensive listening practice.